Research on Security of Routing Protocols Against Wormhole Attack in the Ad hoc Networks - Yang Shengju; Shi Shaoting; Zhao Xinhui (Institute of Advanced Engineering and Science, 2014)
As known that Ad hoc networks are made of a group of portable terminals and has many wireless transmitter as multi-hops autonomy system. While Ad hoc networks are very easy to be attacked by various kinds of network attacks, because it has limited resources, dynamic topology and open communication channel, etc. The wormhole attack is the common attack method, and it is an internal attack against routing protocols in the Ad hoc networks, the research on security of routing protocols against wormhole attack in the Ad hoc networks is to avoid the wormhole attack. In the study, the security routing mechanisms against wormhole attack in the Ad hoc networks are presented, on the basis of deeply research on wormhole attack principles and models. The modelling method and related simulations are presented in detailed to verify the effectiveness of security routing mechanisms. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4062